Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing - Lee, Roger; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book gathers 14 of the most promising papers presented at the 18th IEEE/ACIS International Conference on Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing (SNPD 2017), which was held on June 26-28, 2017 in Kanazawa, Japan. The aim of this conference was to bring together researchers and scientists, businessmen and entrepreneurs, teachers, engineers, computer users, and students to discuss the various fields of computer science and to share their experiences and exchange new ideas and information in a meaningful way. The book presents research findings concerning all aspects (theory, applications and tools) of computer and information science, and discusses the practical challenges encountered along the way, as well as the solutions adopted to solve them.
Sequence Classification based on Active Learning -- Using MongoDB Databases For Training and Combining Intrusion Detection Datasets -- Service Oriented Network Management with Knowledge-Based Network Management System in Fluctuating Environment -- A Topic Structuration Method on Time Series for a Meeting from Text Data -- Joint Embedding of Hierarchical Structure and Context for Entity Disambiguation --  Automatic Optimization of OpenCL-Based Stencil Codes for FPGAs -- Should Duration and Team Size be Used for Effort Estimation? -- A Lifelog Data Portfolio for Privacy Protection based on Dynamic Data Attributes in a Lifelog Service -- Estimation of Emotional Scene from Lifelog Videos in Consideration of Intensity of Various Facial Expressions -- Developing a Framework to Support Designing of Active Learning Class -- Where Do Drivers Look When Driving in a Foreign Country? -- On Password Strength: A Survey and Analysis -- Probabilistic Model-Based Multistep Crossover Considering Dependency betweenNodes in Tree Optimization -- Digital Watermark Design for Two-dimensional Codes Displayed on Smart Phone Screen Using Multi-Objective Optimization and Optical Simulation.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence